Seroprevalence and Predictors of Hepatitis B Virus Infection among Pregnant Women Attending Routine Antenatal Care in Arba Minch Hospital, South Ethiopia. (24th January 2016) - Yohanes, Tsegaye; Zerdo, Zerihun; Chufamo, Nega
Abstract : Hepatitis B virus (HBV) is a serious cause of liver disease affecting millions of people throughout the world. When HBV is acquired during pregnancy, prenatal transmission can occur to the fetus. Therefore, this study is aimed at estimating seroprevalence and associated factors of HBV infection among pregnant women attending Antenatal Clinic (ANC) of Arba Minch Hospital, Southern Ethiopia. A facility based cross-sectional study was conducted on 232 pregnant women visiting ANC from February to April, 2015. Data regarding sociodemographic and associated factors were gathered using questionnaire. Serum samples were tested for hepatitis B surface antigen (HBsAg) by Enzyme Linked Immunosorbent Assay. Data was analyzed using SPSS version 20. The overall seroprevalence of HBV infection was 4.3% (95% CI: 2.2–6.9%). Multivariate analysis showed that history of abortion (AOR = 7.775; 95% CI: 1.538–39.301) and having multiple sexual partners (AOR = 7.189; 95% CI: 1.039–49.755) were independent predictors of HBsAg seropositivity. In conclusion, the prevalence of HBV infection is intermediate. Therefore, screening HBV infection should be routine part of ANC; health information on having single sexual partner for women of childbearing age and on following aseptic techniques during abortion should be provided to health facilities working on abortion.